The Uniqueness of Albumin as a Carrier in Nano Drug Delivery - Yash Gupta; Rai, Vishal; Singh, Anushka; Khan, Soban; Bano, Nisha; Yadav, Reena (Journal for Research in Applied Sciences and Biotechnology, 2024)
The quest for precision medicine hinges on targeted drug delivery, minimizing off-target effects while maximizing therapeutic impact. Among nanocarriers, albumin – the most abundant protein in human blood – emerges as a uniquely biocompatible stealth bomber. Its inherent advantages, including exceptional biodegradability, prolonged circulation, and natural affinity for diseased tissues, perfectly align with the goals of personalized medicine. Albumin readily solubilizes poorly soluble drugs, enhancing bioavailability and broadening the therapeutic arsenal. Its versatile surface allows for targeted modifications, enabling dual diagnosis and treatment (theranostics) tailored to individual needs. While challenges remain in optimizing drug loading and targeting specificity, albumin-based nanocarriers hold immense promise for revolutionizing personalized healthcare, delivering potent therapeutics with pinpoint accuracy. The burgeoning field of nanodrug delivery seeks to redefine therapeutic landscapes by engineering nanoscale carriers that meticulously deliver potent drugs to their designated targets, minimizing systemic exposure and maximizing therapeutic efficacy. This pursuit aligns perfectly with the burgeoning field of precision medicine, where personalized treatments demand exquisite control over drug delivery. Within this intricate choreography, albumin, the abundant and versatile protein resident in human plasma, emerges as a maestro, orchestrating a symphony of advantages that make it a prime candidate for nanocarrier construction.